Criminalization of Maritime Accidents - Sriro, Andrew I. (LAW REVIEW, 2005)
"The safety of navigation, always number one on our priority list, requires the development and updating of standards and procedures covering everything from the structural integrity of ships to their operational features and the training and certification of the crews on board"1 Mr. William A. ONeil (Former Secretary-General of International Maritime Organization, 1990-2